A plant oil‐containing pH 4 emulsion improves epidermal barrier structure and enhances ceramide levels in aged skin. (9th November 2016) - Blaak, J.; Dähnhardt, D.; Dähnhardt‐Pfeiffer, S.; Bielfeldt, S.; Wilhelm, K.‐P.; Wohlfart, R.; Staib, P.
Abstract: Objective: Xerosis is a serious problem among the very old. It is a dermatological challenge caused by significant alterations in stratum corneum (SC) function and structure. Two negative changes in aged skin are (i) the enhanced skin surface pH and (ii) the altered SC lipid content, composition and ordering. Methods: Therefore, we investigated the way in which an acidic skin care product with different plant oils affects SC function, structure and lipid profile in older subjects with dry skin. Before and after a 3‐week application period, different biophysical measurements were performed: transepidermal water loss, SC hydration and skin surface pH. In addition, the SC lipid matrix was evaluated by analysis of the intercellular lipid lamellae and the SC lipid profile. Results: After treatment, a significant increase in lipid lamellae in the intercellular space of the SC was observed in the area treated with the test product compared to the untreated area. Furthermore, the ceramide level was found to be increased, although ceramides were not provided by the acidic test formulation. Conclusion: In summary, topical application of a pH 4.0 product containing plant oils improves epidermal barrier formation and SC lipid ordering and ratio in aged dry skin. Abstract : After treatment with a plant containing pH 4.0 product, a significant increase in lipid lamellae in the intercellular space of the SC was detected. Furthermore, the ceramide level was found to be increased, although ceramides were not provided by the acidic test formulation. In summary, topical application of a pH 4.0 product containing plant oils improves epidermal barrier formation and SC lipid ordering and ratio in aged dry skin.